The problem of symbolic mediation of social understanding in persons who have committed offenses - Abakumova, Polina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The ability to explain and predict the behaviour of other people, to understand their mental states, beliefs, desires is known as the theory of social understanding or the theory of mind. Social understanding is based on the reading and interpretation of symbolic manifestations of human activity. In the works of domestic and foreign authors, it was considered mainly to describe mental development disorders in autism, hearing disorders, in people with depression, and in connection with aging. However, it do not has been studied in persons who have committed offenses and crimes. Social understanding determines the quality and nature of social interaction, as a result, violation of the mental model can play a role in the formation of illegal behaviour. It is important to consider the problem of symbolically mediated social understanding in both offenders and criminals for possible early correction and anticipation of illegal behaviour.
Keywords: social understanding; theory of mind; symbolic mediation; symbol; delinquent behaviour